In Defense of Farmers : The Future of Agriculture in the Shadow of Corporate Power - Alexander, Sara E.; Gibson, Jane W. (Jane Winslow) (Book collections on Project MUSE., 2019)
"Industrial agriculture is generally characterized as either the salvation of a growing, hungry, global population or as socially and environmentally irresponsible. Despite elements of truth in this polarization, it fails to focus on the particular vulnerabilities and potentials of industrial agriculture. Both representations obscure individual farmers, their families, their communities, and the risks they face from unpredictable local, national, and global conditions: fluctuating and often volatile production costs and crop prices; extreme weather exacerbated by climate change; complicated and changing farm policies; new production technologies and practices; water availability; inflation and debt; and rural community decline. Yet the future of industrial agriculture depends fundamentally on farmers' decisions."--Provided by publisher